2016
DOI: 10.1080/09602011.2016.1182032
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prism adaptation on daily life activities in patients with visuospatial neglect: a systematic review

Abstract: Studies that have investigated prism adaptation (PA) effects on symptoms of visuospatial neglect have primarily used neuropsychological tests as outcome measures. An important question that remains to be answered is whether PA effects translate into improvements in patients' daily life activities. In the present review, we examined systematically the evidence for the effect of PA treatment on daily life activities in patients with neglect. Two authors independently assessed the methodological quality of 25 int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 65 publications
2
29
0
1
Order By: Relevance
“…Mirror therapy, or prism adaptation therapy, uses simple equipment to focus a patient’s attention on a neglected hemifield. Mirror therapy, generally provided as an adjunct to conventional therapy, can improve motor function and reduce pain 6 and might improve activities of daily living 7 . Mirror therapy studies have been limited by small sample sizes and methodological limitations.…”
Section: Conventional Therapiesmentioning
confidence: 99%
“…Mirror therapy, or prism adaptation therapy, uses simple equipment to focus a patient’s attention on a neglected hemifield. Mirror therapy, generally provided as an adjunct to conventional therapy, can improve motor function and reduce pain 6 and might improve activities of daily living 7 . Mirror therapy studies have been limited by small sample sizes and methodological limitations.…”
Section: Conventional Therapiesmentioning
confidence: 99%
“…Therefore, neglect rehabilitation remains a challenging problem and currently no rehabilitation approach has been recommended for clinical implementation (Bowen et al, 2013). Nevertheless, significant immediate effects in favour of cognitive rehabilitation vs. control treatments on standardised neglect tests justify the need for further well-designed clinical trials (Bowen et al, 2013; see also Cappa et al, 2005;Champod, Frank, Taylor, & Eskes, 2016;Cicerone et al, 2005;Priftis, Passarini, Pilosio, Meneghello, & Pitteri, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Such asymmetry was also observed as a result of exposing participants to spatial shift by using prism adaptation, which was also proved to assist in shifting the perceived midline of neglect patients (Smith and Bowen, 1980, Adair and Barrett, 2008, Champod et al, 2016. It was suggested that the adaptation process is the fundamental cause for improving neglect symptoms.…”
Section: Hemi-spatial Neglect As a Spatio-temporal Deficitmentioning
confidence: 91%